BENTUK ETNIK JAWA PADA RESTORAN SRIYA CAFE - Fairalsa, Neili; Putri Sekar Hapsari (Institut Seni Indonesia Surakarta, 2024)
Jepara is located in the northern part of Central Java province. Along with economic growth, the city of Jepara has experienced developments in the culinary industry. The fact that people come to restaurants is not just to fulfill their basic needs, namely to eat and drink, but there are other needs to be achieved, namely recreational or leisure activities. The atmosphere of the room or interior decoration is the main factor and differentiator with other restaurants. The purpose of this research is to identify the form of Javanese ethnicity in the forming elements and fillers of Sriya Café Restaurant in Jepara city. Data acquisition techniques through observation, interviews, documentation, and triangulation studies. In this study, the main thing is the visual form of Sriya Cafe Restaurant. While the object in cognition is Javanese ethnicity using descriptive qualitative research design to find the form of Javanese ethnicity in the forming elements and filling elements in the interior of Sriya Café Restaurant. The results of this research show an overview and explanation of the forming elements and atmosphere fillers in the interior of Sriya Café Restaurant, which has a beautiful, open and traditional Javanese atmosphere that has undergone modifications over time but remains consistent with a simple impression. Visitors not only enjoy the food served, but can enjoy the interior atmosphere.Keywords: Restaurant, Elements, Interior, Javanese Ethnic